PELATIHAN E-COMMERCE DAN PENGENDALIAN PERSEDIAAN SPAREPART MENGGUNAKAN LARAVEL FRAMEWORK BAGI SISWA SMK - Hendriani, Sisi; Adha, Afifah Cahayani; Faisal, Muhammad; Ma’ruf, Syaiful (Awal Bros Journal of Community Development, 2024)
The development of information technology has transformed traditional trading systems into digital-based commerce. One of the crucial aspects of e-commerce is the effective management of inventory. This community service activity aims to provide training to students of SMK Labor Kota Pekanbaru in building an e-commerce system while understanding inventory control concepts using the probabilistic inventory method. The training was conducted through lectures, hands-on practices, and interactive discussions using the PHP Laravel Framework. The results showed an improvement in students' understanding of e-commerce application development and the importance of effective stock management. This activity is expected to enhance students' technical skills, prepare them for a digital-based workforce, and encourage innovation in technology-based businesses among the younger generation.